Life, Learning, and Standing Alone: The Adaptation Process of Wives of South Korean Students to New Circumstances - Ju Sung Jun (Adult Education Research Conference, 2002)
The purpose of this study was to explore the cultural meanings and social ramifications of the experiences and understandings of South Korean students’ wives who live in the United States in terms of feminist standpoint and transformative learning.